TRANSFORMASI PELAYANAN DATA PENDIDIKAN MELALUI EFEKTIVITAS KERJA PEGAWAI DI SULAWESI TENGGARA - Sartono; La Ode Muhammad Elwan; La Ode Agus Said; La Ode Aslim (Journal Publicuho, 2024)
The purpose of this writing is to determine the effectiveness of employee work in basic education data services at the Southeast Sulawesi Province Education and Culture Service. This research uses a descriptive qualitative approach method with data collection using interviews, observations and document studies. Using interactive data analysis techniques according to Milles Huberman and Saldana. The research results show that basic education data entry in Southeast Sulawesi Province is carried out by the DAPODIK admin via the official link, with data validation in the DAPODIK room of the Ministry of Education and Culture. Data sorting is managed by the Education and Culture Bureau system and DAPODIK staff. Data services are carried out manually and online according to SOP, even though they are hampered by network problems and power outages. The DAPODIK program has helped speed up the resolution of school, teacher and student data problems, provided convenience for schools and teachers, and reduced community accumulation and paper usage, showing real changes in the education administration process.